2001
DOI: 10.1162/002081801551432
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Aid and Statehood in Africa

Abstract: Has foreign aid destroyed state institutions in Africa? African states depend on development assistance to conduct basic government operations, yet few of these states are well governed or effective at providing public goods. The two trends, mounting foreign aid and static or diminishing state performance, raise an obvious question: Is aid dependency contributing to misrule and state failure in Africa? Many critics argue the two phenomena are related. I find they are not. My analysis fails to show a negative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(119 citation statements)
references
References 40 publications
1
116
0
2
Order By: Relevance
“…Knack and Rahman (2007) Foreign aid can however also lead to better governance, especially if aid is linked to improved governance and provides technical support towards good governance and generally by aiding in human development of the recipient countries (Ear, 2007). Goldsmith (2001) found that higher aid/GDP ratio is associated with higher levels of democratic performance and economic freedom in sub-Saharan Africa. Dunning (2004) found that when the sample used in Goldsmith (2001) is disaggregated into the Cold-War and post-Cold War periods, the positive relationship between aid and democratization in sub-Saharan Africa holds only in the latter period.…”
Section: Wwwccsenetorg/ibrmentioning
confidence: 99%
See 2 more Smart Citations
“…Knack and Rahman (2007) Foreign aid can however also lead to better governance, especially if aid is linked to improved governance and provides technical support towards good governance and generally by aiding in human development of the recipient countries (Ear, 2007). Goldsmith (2001) found that higher aid/GDP ratio is associated with higher levels of democratic performance and economic freedom in sub-Saharan Africa. Dunning (2004) found that when the sample used in Goldsmith (2001) is disaggregated into the Cold-War and post-Cold War periods, the positive relationship between aid and democratization in sub-Saharan Africa holds only in the latter period.…”
Section: Wwwccsenetorg/ibrmentioning
confidence: 99%
“…Economic development can generate tax revenues for public coffers, which can improve the quality of governance by alleviating funding constraints (Goldsmith, 2001;Knack, 2001;Brä utigam & Knack, 2004;Dunning, 2004;Ear, 2007). The legal, judicial and other civil administration systems in countries that experienced long history of European colonialism can be different from other countries (Goldsmith, 2001;Dunning, 2004). A dummy variable has been added to account for the European colonial history of the sample countries.…”
Section: Quality Of Governance It = α + β 1 Foreign Aid It + β 2 Edmentioning
confidence: 99%
See 1 more Smart Citation
“…Democratic practices have been expanding around the world, with support and encouragement of the donor community (Goldsmith, 2001). Competitive democratic or democratizing regimes are more likely to: have open political and governing structures that are responsive to citizens, and create the circumstances that would allow civil society groups to organize freely and to participate in the policy process.…”
Section: Macroeconomic Policy and Participationmentioning
confidence: 99%
“…Therefore, the purpose of this article is to consider foreign aid and its implications for processes of democratization in recipient countries. Current studies are not unanimous and opinions range from those that support the idea that foreign aid increases (at least, under certain circumstances) the likelihood of regime transformations, 4 to those that claim that there foreign aid has no significant impact on regime dynamics, 5 and, finally, to those that claim that foreign aid makes democratization less probable. 6 …”
mentioning
confidence: 99%